Evaluation of the effects of ethyl cellulose and polyvinyl alcohol mass ratio on the characteristic of simvastatin-loaded polymer-based matrix patch for transdermal delivery - Alviola, Inna Marie E.
Simvastatin (SMV) is a widely prescribed statin that lowers cholesterol levels and is commonly available in its oral dosage form. However, SMV has a low bioavailability due to first-pass metabolism, making it a suitable candidate for transdermal drug delivery. The study aimed to screen the factors that mainly affect the release and permeation of SMV from the SMV-loaded transdermal patch (SMV-TDDS). Compatibility of the formulation components was evaluated through thin layer chromatography. SMV patches were prepared by the solvent casting method. The patches were characterized based on thickness, weight, folding endurance, moisture content, SMV content, and adhesion. In vitro drug release was performed via USP dissolution apparatus 5. In vitro skin permeation was performed using the Franz diffusion cell with Strat-M° as membrane. SMV and excipients were compatible. The fabricated transdermal patches exhibited satisfactory qualities overall, with the exception of their adhesion characteristics. In vitro dissolution studies suggest all formulations with varying EC:PVA ratios exhibited controlled release profiles. F4 released the maximum quantity of SMV (95.30 ± 2.96%) after 24 hours. In vitro permeation studies suggest that varying EC to PVA mass ratio can affect SMV permeation, with F5 showing the highest permeation at 16.38%. F5 also had the highest micro flux of 0.6964 ng/em2h. Transdermal patches can be successfully fabricated using the SMV and the excipients used in this study. Varying ratio of EC and PVA can affect the release and permeation of the fabricated SMV-TDDS. We recommended some modifications on the levels of polymer mass ratio to determine which level would exhibit maximum release and permeation, and thus can be used for the optimization studies.